2019
DOI: 10.1038/s41598-019-46933-y
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-1 is required for Coxsackie Virus B3-induced inflammation in pancreatitis

Abstract: The Muc-1 oncoprotein is a tumor-associated mucin often overexpressed in pancreatic cancer. We report that knockout of Muc-1 reduced the degree of pancreatic inflammation that resulted from infection with Coxsackievirus B3 (CVB3) in a mouse model. CVB3-infected Muc-1-deficient (Muc-1 KO ) mice had significantly reduced infiltration of macrophages into the murine pancreas. We found that Muc-1 signaling through NF-κB increased expression of ICAM-1, a pro-inflammatory mediator that recruits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…55,56 The cell surface MUC1 extracellular domain expressed on leukocytes has also been demonstrated to mediate trans-endothelial cellular migration of Mɸs by binding to endothelial ICAM-1, 57,58 partly by instigating Src-CrlL-Rac1/Cdc42 facilitated actin cytoskeletal protrusive motility. 59,60 Although a lower level of ICAM-1 expression in the Muc1 deficient pancreas leads to reduction of infiltration of Mɸs in a coxsackie virus B3infection model, 61 we did not observe a difference of expression of Icam1 between WT and Muc1 deficient colonic tissues during AOM/DSS treatment.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…55,56 The cell surface MUC1 extracellular domain expressed on leukocytes has also been demonstrated to mediate trans-endothelial cellular migration of Mɸs by binding to endothelial ICAM-1, 57,58 partly by instigating Src-CrlL-Rac1/Cdc42 facilitated actin cytoskeletal protrusive motility. 59,60 Although a lower level of ICAM-1 expression in the Muc1 deficient pancreas leads to reduction of infiltration of Mɸs in a coxsackie virus B3infection model, 61 we did not observe a difference of expression of Icam1 between WT and Muc1 deficient colonic tissues during AOM/DSS treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…Our findings are supported by a recent investigation showing Muc1 -deficient BMDMs had reduced Ccr2 expression, resulting in decreased LPS-induced migration in a coxsackie virus B3-infection model. 61 Thus, our results suggest that MUC1 contributes to colonic tissue Mɸ infiltration by enhancing both epithelial and Mɸ CCL2 production and by promoting Mɸ migration responses to CCL2.…”
Section: Discussionmentioning
confidence: 55%
“…Much research has shown that abundant neutrophils and macrophages are produced and recruited into the mouse pancreas during early CVB3 infection, secreting various cytokines, including IL-1β, IL-6, and TNF-α. 11,35 Then, massive acinar cell destruction is seen in the pancreas of mice, which develop acute pancreatitis. 36 In addition, CVB3 infection is known to induce cellular apoptosis.…”
Section: Papermentioning
confidence: 99%
“…6,7 CVB3 may spread from the intestinal tract to internal organs such as the pancreas and heart, causing pancreatitis 8 and myocarditis 9,10 ranging from mild to severe, including acute and chronic inflammation. 11,12 However, there remain no efficient vaccines or antivirals for treating pancreatitis caused by CVB3, highlighting the need for investigating new strategies to treat pancreas lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However its physiological significance remains to be verified. Many viruses, including hepatitis viruses [ 77 ], human immunodeficiency virus [ 78 ], epstein-barr virus, [ 79 ] and coxsackie virus [ 80 ], can also cause pancreatitis. Among these viruses, coxsackie virus B3 (CVB3) infection has been reported to induce an increase on the levels of intracellular Ca 2+ as well as cytoskeleton depolymerization in host cells, promoting the secretion of CVB3-positive exosomes that may propagate virus transmission upon uptake by non-infected cells.…”
Section: Exosomes and Paca Initiationmentioning
confidence: 99%